Pertumbuhan dan Hasil Kubis Bunga pada Sistem Hidroponik Substrat dengan Media Bagase - Ade Imam Mustofa; Djoko Purnomo; Amalia Tetrani Sakya (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2018)
Cauliflower is one of the popular vegetables and has high economic potential. The need for vegetables is high but the productivity is increasingly starting to decline due to narrow land. Hydroponic technology does not require fertile are. Hydroponics of cauliflower expected to increase economic value. Bagasse has characteristics wet and easy to absorb water is very suitable as a media hydroponic substrate. The experimental research was held out from August 2016 until February 2017 in the screen house of the Faculty of Agriculture, Sebelas Maret University, Surakarta The experiments using complete randomized design with 2 treatment factors consisted of various nutrients (2 types) and media (3 types) resulting in 6 treatment combinations, each repeated 3 times. Nutrient types are standard nutrients and modified nutrients (standard K reduction nutrients).The types of media types are bagasse, bagasse + gravel, and bagasse + red brick fractions. Bagasse + fragment red brick showed better yield on volume of root, large of leaf, biomass of plant and age of flower. While the highest of plant on media bagasse + gravel.